Pengaturan Hukum Penambahan Penyertaan Modal Negara ke dalam Lembaga Pengelola Investasi Menurut Peraturan Pemerintah Nomor 111 Tahun 2021 - Muhammad Abdi Dermawan; Ransya Ayu Zulvia; Deni Kamaludin Yusup (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2026)
The addition of State Capital Participation (PMN) into the Investment Management Agency (LPI) under Government Regulation Number 111 of 2021 represents a strategic legal policy aimed at strengthening Indonesia’s investment capacity and the capital structure of its sovereign investment institution. This study employs a normative juridical approach by analyzing statutory regulations, legal doctrines, and relevant academic literature to examine the legal framework, conceptual implications, and economic law perspective of PMN within LPI governance.The findings indicate that PMN affirms LPI’s status as a sui generis legal entity operating under private (civil law) principles while managing assets derived from state finances, thereby creating a normative tension between state financial law principles—such as transparency, accountability, and public oversight—and the flexibility of investment management practices. Although the policy enhances the state’s ability to consolidate strategic assets, attract investment, and accelerate economic development, LPI’s legal privileges, including immunity from asset seizure and limited direct supervision by the Audit Board of Indonesia (BPK), pose risks to fiscal control and public accountability. From an economic law perspective, the policy is justifiable as maslahah only if implemented in line with principles of justice, trustworthiness, and public benefit, thus requiring strengthened governance and oversight mechanisms.